Oblicz.
a) (−7) ⋅ 5 = b) 54 :(−6) = c) (−3) ⋅ (−4) = d) (−32) :(−8)
zad. 2
Wartość wyrażenia −3 + (−2) ⋅ (−7) jest równa:
Zad. 3
Oblicz:
a) 24 :(−3) ⋅ (−4) =
b) (−9) ⋅ 0 − 32 :(−8) =
c) 8⋅(−18) + (−16)
−5 =


Odpowiedź :

Odpowiedź:

1.

a. -35

b. -9

c. 12

d. 4

2.

-3+(-2)×(-7)= -3+14= 17

3.

a. 32

b. 4

c. -165

Odpowiedź:Oblicz.

a) (−7) ⋅ 5 = -35

b) 54 :(−6) = -9

c) (−3) ⋅ (−4) = 12

d) (−32) :(−8)= 4

Zadanie 2.

−3 + (−2) ⋅ (−7) = -3+14= 11

Zad. 3

Oblicz:

a) 24 :(−3) ⋅ (−4) = (-8) ⋅ (-4)= 32

b) (−9) ⋅ 0 − 32 :(−8) = 0-(-4)= 0+4=4

c) 8⋅(−18) + (−16) −5 = -144+(-21)= -165

Szczegółowe wyjaśnienie: